Jumping ability is related to change of direction ability in elite handball players - Katsumata, K.; Aoki, K. (Journal of Electromyography and Kinesiology, 2021)
Purpose: This study investigated the relationship between vertical and horizontal jumping ability and change of direction (COD) to measure athletic performance in 51 elite male handball players.